2021
DOI: 10.3390/d13120673
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Citizen Science in the Research and Management of Invasive Lionfish across the Western Atlantic

Abstract: Managing invasive Indo-Pacific lionfish (Pterois volitans and P. miles) in the Western Atlantic Ocean is beyond the capacity of natural resource organizations alone. In response, organizations have mobilized members of the public and citizen scientists to help. We used a structured survey to assess the activities and perceptions of 71 organizations that engage the public and citizen scientists in lionfish research and management throughout the invaded range of the Western Atlantic. Five case studies were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 78 publications
1
12
0
Order By: Relevance
“…Although market-based approaches have been used in the region with mixed results (Chapman et al, 2016;Quintana et al, 2022), a well-managed one could contribute significantly to the conservation of Florida's marine ecosystems, especially coral reefs that have been negatively impacted by invasive lionfish. Given that regular removal of lionfish has been the most effective tool used thus far (Clements et al, 2021), our study indicates that improving the restaurant supply chain for invasive lionfish can help control its population, thereby reducing negative ecological impacts. The utilization of market approaches to eradicate lionfish in Florida could have compounding positive impacts on native reef systems in the Western Atlantic at large by potentially preventing further impacts, and improving the health of key marine fish stocks, habitats and critical marine ecological systems (Duarte et al, 2020).…”
Section: Conservation Benefitsmentioning
confidence: 91%
See 1 more Smart Citation
“…Although market-based approaches have been used in the region with mixed results (Chapman et al, 2016;Quintana et al, 2022), a well-managed one could contribute significantly to the conservation of Florida's marine ecosystems, especially coral reefs that have been negatively impacted by invasive lionfish. Given that regular removal of lionfish has been the most effective tool used thus far (Clements et al, 2021), our study indicates that improving the restaurant supply chain for invasive lionfish can help control its population, thereby reducing negative ecological impacts. The utilization of market approaches to eradicate lionfish in Florida could have compounding positive impacts on native reef systems in the Western Atlantic at large by potentially preventing further impacts, and improving the health of key marine fish stocks, habitats and critical marine ecological systems (Duarte et al, 2020).…”
Section: Conservation Benefitsmentioning
confidence: 91%
“…In Florida specifically, it can evolve solutions to the barriers that prevent the lionfish fishery from scaling up (Clements et al, 2021).…”
Section: Encouraging and Establishing Partnerships Centered On Conser...mentioning
confidence: 99%
“…For lionfish management, this has included volunteers, citizen scientists, fishers, seafood wholesalers and retailers, chefs, students and local citizens. Stakeholder participation in lionfish research has been particularly effective for facilitating monitoring and control efforts for collecting specimens, reporting observations, and the dissemination of information (Clements et al, 2021). For example, in Bonaire, culled lionfish were used to study their invasion ecology, and partnerships were formed between the management agency (Stichting Nationale Parken Bonaire), a research facility (CIEE Research Station, Bonaire), dive operators, and volunteer divers (Ali, 2017).…”
Section: Community and Stakeholders Should Be Engaged To Facilitate L...mentioning
confidence: 99%
“…The risk of abuse was mitigated by (1) gear restrictions that mandated use of short pole spears (e.g., less than 1 m in length), which are largely ineffective in harvesting most other fishes, and (2) pursuing a participatory approach by working with scuba divers, local stakeholders and organizations. These participatory management approaches for lionfish removals, monitoring, and research appear to have largely resulted in cumulative positive social, economic, and ecological effects (Reed, 2008;Clements et al, 2021). In the Mediterranean, lionfish management in Cyprus [e.g., The Underwater Research and Imaging Center (URIC) and RELIONMED projects] has demonstrated similar successes for awareness programs, control, monitoring and data collection (Kleitou et al, 2019;Kleitou et al, 2021a).…”
Section: Policy Changes To Permit Lionfish Removalmentioning
confidence: 99%
“…Controlling invasive lionfish (Pterois volitans/miles complex) populations is a major objective for marine conservation and fishery managers in the western Atlantic Ocean (Morris et al, 2012;Hixon et al, 2016;Sutherland et al, 2017) and the Mediterranean Sea (Kletou et al, 2016;Savva et al, 2020;Ulman et al, 2020). To date, removal efforts have primarily utilized spearfishing by SCUBA divers (Morris et al, 2012;Clements et al, 2021), which can efficiently remove lionfish (Usseglio et al, 2017;Harris et al, 2019;Ulman et al, 2022) and reduce local lionfish densities regions (Green et al, 2014;Harms-Tuohy et al, 2018;Harris et al, 2019). Market demand for invasive lionfish has also increased (Blakeway et al, 2019;Blakeway et al, 2021;Bogdanoff et al, 2020), and commercial fisheries have developed for lionfish in some areas (Chapman et al, 2016;Harris et al, 2020a;Ulman et al, 2022).…”
Section: Introductionmentioning
confidence: 99%